Subjective Career Success in The Modern Career: A Parallel Mediation of Perceived Internal and External Employability - Syahrizal Syahrizal; Tika Rahma Yani Siregar (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: There has been a notable shift in career theory, whereby traditional career paths, which were largely determined by an employee's initial training and investment from the employer, have shifted towards modern career paths that are largely guided by the employee themselves. This shift is accompanied by a change in the contemporary workforce, where success is now characterised by a stronger focus on subjective aspects. Purpose: This study investigates the impact of perceived organizational support and perceived employability on the subjective career success among independent workers in Hajj and Umrah travel companies in West Sumatra. It also explores the parallel mediating effects of perceived internal and external employability. Design/methodology/approach: This quantitative investigation was conducted using a survey approach. The study involved 210 participants, and data collection was conducted through the utilisation of a questionnaire. To test the hypotheses, a quantitative approach incorporating structural equation modelling (SEM) was employed using SmartPLS 4.0. Findings/Result: The research findings indicate that perceived organizational support has a positive influence on subjective career success. We also discovered that perceived external employability influenced subjective career success, whereas perceived internal employability did not. The results also show that perceived external employability plays a mediating role in the relationship between perceived organizational support and subjective career success. Conclusion: The research findings indicate that individuals exhibit a higher level of sensitivity towards their subjective career success when it comes to external options, as opposed to internal ones. Originality/value (state of the art): This study expands the existing literature by exploring parallel the mediation of perceived internal and external employability. Keywords: independent workers, perceived internall employability, perceived externall employability, perceived organizationall support, subjective career successs